The Museum in the Age of Experience (DAPesquisa, 2025)
The present article discuss the relations between museum and public, through participation and experience. This paper presents general concepts of experience from the perspective of memory and emotions, then discuss the experience in the scope of design and the approaches of experience design. In addition, it draws a historical panorama of the space-public-experience relations, reinforcing the idea of ​​involving the public through experience to make the museum more accessible. The present article presents the exhibition “Obsession Infinite”, by artist Yayoi Kusama for an example of how the experience materializes in the museum space